1982
DOI: 10.1161/01.cir.66.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Increased exercise tolerance and reduced electrocardiographic ischemia with diltiazem in patients with stable angina pectoris.

Abstract: SUMMARY Diltiazem is a calcium slow-channel blocking drug that may be effective in the treatment of chronic stable angina pectoris. To evaluate the therapeutic efficacy 3 hours after a single oral dose of 120 mg, 12 men with chronic stable angina pectoris performed a maximal exercise test on a bicycle ergometer after ingesting either placebo or diltiazem administered in a double-blind fashion. During submaximal exercise at a fixed work load, diltiazem decreased the average heart rate response from 119 ± 17 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(8 citation statements)
references
References 23 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…On propranolol alone the mean plasma propranolol concentration was 118 ng/ml (range 64 to 183) and in combination with diltiazem it was 109 ng/ml (range 23 to 180 THERAPY AND PREVENTION-CORONARY ARTERY DISEASE ment in exercise capacity with an increase in dose levels from 120 mg to 240 mg/day. Single-dose studies in which as much as 120 mg diltiazem was used15 16 have shown no associated significant adverse effects. Consequently, we wanted to examine the short-term safety and efficacy of high-dose diltiazem (90 mg four times daily) in patients with stable effort angina.…”
Section: Resultsmentioning
confidence: 99%
“…On propranolol alone the mean plasma propranolol concentration was 118 ng/ml (range 64 to 183) and in combination with diltiazem it was 109 ng/ml (range 23 to 180 THERAPY AND PREVENTION-CORONARY ARTERY DISEASE ment in exercise capacity with an increase in dose levels from 120 mg to 240 mg/day. Single-dose studies in which as much as 120 mg diltiazem was used15 16 have shown no associated significant adverse effects. Consequently, we wanted to examine the short-term safety and efficacy of high-dose diltiazem (90 mg four times daily) in patients with stable effort angina.…”
Section: Resultsmentioning
confidence: 99%
“…Although calcium antagonists are now universally only in chemical structure but also in terms of recognized as major therapeutic agents in their negative inotropic effects or their effects on ischaemic heart disease (Hugenholtz et al, 1981; myocardial relaxation, coronary blood flow, and Gunther et al, 1981;Zacca et al, 1982;Rouleau oxygen consumption (Rousseau et al, 1980(Rousseau et al, , et al, 1983Wagniart et al, 1982;Braunwald, 1981;Walsh & O'Rourke, 1983;Gelpi et al, 1983), the pharmacologic profile of the ideal 1983; Rouleau et al, 1983; Emanuelsson & calcium antagonist to treat angina pectoris Holmberg, 1983;Krebs, 1984). remains ill defined.…”
Section: Introductionmentioning
confidence: 99%
“…Dose titration studies have shown that beneficial effects of diltiazem can be demonstrated by exercise treadmill testing in patients with coronary artery disease at doses of 240 mg/day, but not at lower doses. "7 Single doses of 90 to 120 mg have also been demonstrated to be effective.8 9 Little data exist concerning the effects of higher doses of diltiazem (360 mg/day) on resting hemodynamics and left ventricular performance during exercise. Therefore, the purpose of this study was to evaluate the safety, efficacy, and hemodynamic effects of 360 mg/day diltiazem in divided doses for the treatment of chronic stable exertional angina pectoris.…”
mentioning
confidence: 99%